Behind Brazilian "racial democracy" racism, culture and black identity in Brazil - Agier, Michel (My University, 1994)
In this paper, we tried to understand the recent transformations of racial and cultural fields in Brazil, specially in Bahia, the most black city in Brazil. Firstly, the historical formation of racism is examined, through relations and values issued from slavery, scientist theories, whitening policy and the myth of racial democracy. Then, the usages of cultural african heritage are discussed to understand the current formation of new identity models among Afro-Brazilian people.
Paper : Democracy: Popular Precedents, Popular Practice and Popular Culture. Johannesburg, 1994 : History Workshop / University of the Witwatersrand
Keywords: Brazil; Racism; Bahia; African heritage; Afro-Brazilians